The Seven-year Journey of an Ectopic Canine: Multidisciplinary Management of a Dentigerous Cyst in the Early Mixed Dentition. (2nd November 2021) - Colloc, Thibault; Morrison, Roderick; Burrell, Mark; Larmour, Colin
Abstract : The Aberdeen Royal Infirmary oral and maxillofacial surgery department is involved in the joint planning of cases with the orthodontic and restorative departments of the Aberdeen Dental Hospital to agree an optimal treatment plan for patients, with input from all three specialties. A 7-year-old girl was referred to the orthodontic department by her GDP due to non-eruption of the upper left central incisor. This was related to an associated dentigerous cyst. This presentation illustrates the phases of treatment involving marsupialization of the dentigerous cyst; surgical extraction and orthodontic treatment in order to provide the patient with the optimal outcome for her dentition. A retrospective assessment of the case is presented through photographs and radiological imaging outlining the chronology of the treatment and the outcome of marsupialization of the dentigerous cyst. It highlights this more conservative surgical approach as giving the best chances of preserving unerupted teeth in a younger patient. Marsupialization of a dentigerous cyst associated with UL1 and conservative management of cystic pathology led to preservation and natural mesial eruption of UL3 into the position of UL1. The unerupted UL1 associated with cystic pathology was extracted due to its ectopic position and root dilaceration. Seven years after diagnosis of the dentigerous cyst associated with the unerupted UL1, surgical and orthodontic management has facilitated the for patients tooth to erupt into the UL1 position. Restorative treatment is being planned following orthodontic treatment to restore for patients tooth to simulate the missing UL1. CPD/Clinical Relevance: This case encourages the appropriate referral of young patients with dentigerous cysts to achieve a satisfactory outcome.